Enzyme-Assisted Extraction of Fucosylated Chondroitin Sulfate from Sea Cucumber Holothuria scabra and Bohadschia argus and their Potential in Pharmaceutical Applications - Rattanaporn, Kittipong; Ruensodsai, Thanagorn; Mensah, Richard Q.; Vasudevan, Shrivarshini; Shanmugam, Ratheeshkumar; Venkatachalam, Ponnusami; Kitiborwornkul, Nichaphat; Sriariyanun, Malinee (Applied Science and Engineering Progress, 2024)
Due to the health benefit of fucosylated chondroitin sulfate (FuCS), the efficient method for extraction of FuCS from raw materials is a crucial issue in reducing the production cost. In this study, enzymatic extraction of FuCS from two species of sea cucumber, Holothuria scabra and Bohadschia argus was undertaken using two protease enzymes, alcalase and papain. Response surface methodology (RSM) was employed in determining the optimal extraction conditions with the highest yield of FuCS concentration. The predicted optimal papain-assisted extraction conditions of Holothuria scabra and Bohadschia argus obtained a predicted FuCS yield of 1609.73 mg/100 g and 444.51 mg/100 g, respectively. To compare extraction efficiencies of two protease enzymes, employment of the RSM optimal conditions to Holothuria scabra resulted in 1538.76 ± 20.26 mg/ 100 g and 1295.50 ± 14.28 mg/100 g of purified FuCS for papain and alcalase, respectively. Whereas Bohadschia argus produced 412.39 ± 10.12 mg/100 g and 461.11 ± 8.45 mg/100 g purified FuCS for papain and alcalase, respectively. The acquired FTIR and NMR spectrums of extracted FuCS showed typical bands of sulfation patterns and were compared to commercial FuCS. The extracted FuCS showed enzyme type dependent antioxidant activity, and significant tyrosinase inhibitory activity than commercial FuCS. It also exhibited similar anti-glucosidase activity as commercial FuCS. Thus, this study reveals potential applications of enzyme-assisted FuCS from sea cucumber in food and pharmaceutical industries.